Interpersonal networks and the archaeology of social structures; using social positioning events to understand social strategies and individual behaviour - Joaquim Carvalho; Rosário Campos (Revista de História da Sociedade e da Cultura)
This paper is based on two community reconstitution studies (Soure and Lousã) in early modern Portugal during the 17th and 18th centuries that demonstrate the value of analyzing networks of relationships, especially the "apadrinhamento" (selecton of godparents), in understanding social structures and the individual strategies that they encompass.